2011
DOI: 10.2337/dc11-0807
|View full text |Cite
|
Sign up to set email alerts
|

Location, Location, Location: Geographic Clustering of Lower-Extremity Amputation Among Medicare Beneficiaries With Diabetes

Abstract: OBJECTIVELower-extremity amputation (LEA) is common among persons with diabetes. The goal of this study was to identify geographic variation and the influence of location on the incidence of LEA among U.S. Medicare beneficiaries with diabetes.RESEARCH DESIGN AND METHODSWe conducted a cohort study of beneficiaries of Medicare. The geographic unit of analysis was hospital referral regions (HRRs). Tests of spatial autocorrelation and geographically weighted regression were used to evaluate the incidence of LEA by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
137
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(154 citation statements)
references
References 20 publications
3
137
0
3
Order By: Relevance
“…The indication for an LEA is as variable as is the procedure itself (e.g., the part of the lower extremity removed). Recently, it was reported that the annual incidence of LEA is between 4 to 5 per 1,000 personyears in 5 million beneficiaries with diabetes in the U.S. Medicare population between 2006 and 2008 (14). There was also a three-to fivefold geographic variation in amputation incidence (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The indication for an LEA is as variable as is the procedure itself (e.g., the part of the lower extremity removed). Recently, it was reported that the annual incidence of LEA is between 4 to 5 per 1,000 personyears in 5 million beneficiaries with diabetes in the U.S. Medicare population between 2006 and 2008 (14). There was also a three-to fivefold geographic variation in amputation incidence (14).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the annual incidence of LEA is between 4 to 5 per 1,000 personyears in 5 million beneficiaries with diabetes in the U.S. Medicare population between 2006 and 2008 (14). There was also a three-to fivefold geographic variation in amputation incidence (14). Similarly, a study in 2012 by Holman et al (27) demonstrated an incidence of LEA in those with diabetes of ;2.5 per 1,000 person-years and also noted an eightfold geographic variation in LEA rates among the Primary Care Trusts in England.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Az Amerikai Egyesült Államok, Egyesült Királyság, valamint Finnország által közölt adatok szerint az adott ország különböző terüle-teinek amputációs incidenciaadatai 1,3-8,6-szeres kü-lönbséget mutathatnak [19,23,24]. Ezeknek a vizsgála-toknak az eredményei térségi autokorrelációt jeleztek, azaz az egymással szomszédos területek incidenciaadatai jellemzően közelebb állnak egymáshoz, mint az egymás-tól távoli területeké [23].…”
Section: Alsó Végtagi Amputációk: Előfordulás Trendek a Világbanunclassified
“…Variation exists both between countries and within a country. For example, there is an approximate twofold variation in the incidence of LEA between the U.K. and the U.S. (5,7). A study published in 2011 (5) in the U.S. demonstrated a nearly fourfold variation within the U.S. and further showed that increased incidence of LEA was clustered in contiguous regions within the U.S.…”
mentioning
confidence: 99%